Convergent Associative Motor Cortical Plasticity Induced by Conditional Somatosensory and Motor Reaction Afferents - Huang, Yi; Chen, Jui-Cheng; Tsai, Chon-Haw; Lu, Ming-Kuei (Frontiers in Human Neuroscience, 2020)
Objective: Associative motor cortical plasticity can be non-invasively induced by paired median nerve electric stimulation and transcranial magnetic stimulation (TMS) of the primary motor cortex (M1). This study investigates whether a simultaneous motor reaction at the other hand advances the associative plasticity in M1. Methods: Twenty-four right-handed subjects received conventional paired associative stimulation (PAS) and PAS with simultaneous motor reaction (PASmr) with at least one-week interval. The PASmr protocol additionally includes left abductor pollicis brevis muscle movement responding to a digital sound. The motor reaction time was individually measured. The M1 excitability was examined by motor evoked potential (MEP), short-interval intracortical inhibition (SICI) and intracortical facilitation (ICF) before and after the PAS protocols. Results: The conventional PAS protocol significantly facilitated MEP and suppressed SICI. A negative correlation between the reaction time and the MEP change, and a positive correlation between the reaction time and the ICF change were found in the PASmr protocol. By subgrouping analysis, we further found significant facilitation of MEP and reduction of ICF in the subjects with fast reaction time but not in those with slow reaction time. Conclusion: Synchronized motor reaction ipsilateral to the stimulated M1 induces associative M1 motor plasticity through the spike-timing dependent principle. MEP and ICF change could represent such kind of plasticity. The current findings provide a novel insight into designing rehabilitation programs concerning motor function.